The Influence of AHTS Vessel Maintenance on Operational Efficiency at Pertamina Marine Solutions - Harmuzan, Harmuzan; Dapot Diaman; Mardiana, Mardiana; Boy Laksmana; Ihram Wiratantri (Pusat Riset dan Inovasi Nasional, 2025)
This research investigates how maintenance of Anchor Handling Tug Supply (AHTS) vessels and the availability of spare parts affect operational efficiency in Pertamina Marine Solutions’ Transko Andalas activities. Using a qualitative approach, the study engaged maritime experts, engineers, and operational supervisors to identify essential determinants of vessel performance and continuity. Data collection was conducted through semi-structured interviews, focus group discussions, and thematic analysis, which provided insights into maintenance issues and their direct implications for daily operations. The findings show that operational efficiency improves significantly when preventive maintenance is carried out consistently and supported by reliable spare parts availability. Conversely, delays in spare parts procurement, shortages of skilled technical staff, and gaps in maintenance expertise are found to weaken vessel reliability. The study makes an important contribution to the field of maritime transportation management by offering practical, evidence-based maintenance guidelines and emphasizing the importance of developing human resources for specialized offshore support vessels. In addition, the research highlights several practical measures, including the establishment of stronger maintenance systems, the provision of comprehensive training for technical personnel, and the optimization of supply chain strategies to ensure timely spare parts readiness. These implications provide valuable direction for enhancing operational performance and sustainability within the Indonesian maritime sector, particularly in complex offshore support operations where efficiency and reliability are critical.